ANALISIS KEMAMPUAN MEMBACA NYARING SISWA KELAS II SD NEGERI 3 UBUNG MELALUI TEKS CERITA - Goreti Rini Kristiantari, Maria; Chindytia; Luh Gde Tian Tantrini, Ni; Parahita Niken Mahayu, Putu; Nyoman Widhiastuti, Ni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading aloud is a fundamental skill that must be mastered by elementary school students, particularly in lower grades, as it supports the development of reading fluency, pronunciation, and comprehension. Second graders at SD Negeri 3 Ubung were the subjects of this research, which sought to evaluate their capacity to read tale texts aloud. The study described students' reading ability in detail using a descriptive qualitative approach backed by basic quantitative data. This research included 27 second graders from SD Negeri 3 Ubung.Reading aloud markers of fluency, pronunciation correctness, intonation, voice volume, and tale text comprehension were used to gather data via observation and recording. Based on these factors, we were able to classify each kid as either competent or not capable. The data was analysed using descriptive qualitative analysis, which was backed up by percentage calculations and frequency distribution, to bolster the conclusions. The findings revealed that out of the total number of pupils, 23 (or 85.19 percent) were classified as having the ability to read aloud, while 4 (14.8 percent) were classified as having no such ability. Based on these results, it seems that most kids had no problem reading tale materials aloud. Nevertheless, some students still need more help with fluency, pronunciation, and understanding, so they may improve. Overall, second graders at SD Negeri 3 Ubung have decent reading aloud skills, but those who haven't quite mastered the skill yet can benefit from further practice and encouragement from their teachers.